2022
DOI: 10.1177/13506501221113154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grease grades on the tribological and vibrational behaviours of a radial ball bearing: Conventional vs. micro-grooved outer races

Abstract: Comparative tribo-dynamic studies of radial ball bearings possessing micro-grooved and conventional outer races, employing three different grades of lithium soap-based greases (NLGI grade 000, 2 and 3), are presented in this paper. This research has been conducted to explore and understand the effectiveness of grease grades on the performance parameters in the presence of a circumferential micro-groove on the outer race as compared to conventional case. Indication of lubricating film thickness formation (in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…34 It is also understood that presence of air in circumferential micro-groove also must have played the cooling effect by removing heat from the contacts that led to the improved performances. 35 Thus, sharing of the applied load at two locations and circulation of air through the micro-groove at the outer race of MGB are mainly responsible for improving the performance. Figure 17(a) to (c) illustrate all possible mechanisms/situations that have helped in improving the performance behaviors of micro-grooved race bearing as compared to conventional raced bearing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 It is also understood that presence of air in circumferential micro-groove also must have played the cooling effect by removing heat from the contacts that led to the improved performances. 35 Thus, sharing of the applied load at two locations and circulation of air through the micro-groove at the outer race of MGB are mainly responsible for improving the performance. Figure 17(a) to (c) illustrate all possible mechanisms/situations that have helped in improving the performance behaviors of micro-grooved race bearing as compared to conventional raced bearing.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the bearing has been tested by employing three different grease grades (NLGI 000, 2, and 3), and improvement in tribodynamic and vibration results have been reported in comparison to the CB. 35 However, it is also understood that the evaluation of its fatigue life is essential for comparing with identical CBs. Hence, the aim of this research was set to carry out long duration test of both the bearings (CB and MGB) in dry conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The role of circumferential micro-groove on the stationary outer race in a radial deep groove ball bearing has been experimentally explored. 22,23 In comparison to conventional bearing cases, about 41% reduction in vibrations, up to 11% increase in film thickness and a maximum of 30% reduction in the frictional torque have been reported. Textures possessing the shapes of micro-cylindrical and elliptical dimples have been machined at the gear flank to investigate its influence on the tribo-dynamic behaviours of gearsets.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning here that surface textures and microgrooves are being used in the products (mainly rolling bearings and gearsets) possessing the concentrated contacts in addition to the ongoing research with generic concentrated textured contacts. Some researchers have employed textures on races of ball bearings [18][19][20][21][22][23] and gearsets, 24,25 and it has been demonstrated that the presence of textures in the products is beneficial in terms of reduced friction and vibrations. Textures created on the races of a thrust ball bearing lubricated with grease yielded a significant reduction in frictional torque, vibrations and temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…Friction torque is an important index to predict bearing life (Jin et al, 2021;Sun et al, 2023); in recent decades, a series of studies have been carried out on the test of bearing friction torque. For example, Gouda et al (2023aGouda et al ( , 2023bGouda et al ( , 2022 proposed a ball roller bearing with microgroove, built a test instrument for the ball roller bearing and compared the proposed bearing with conventional bearing with the test instrument. Under different lubricants, rotational speeds and radial pressures, the friction torque, vibration, temperature rise and surface damage of the bearings were tested.…”
Section: Introductionmentioning
confidence: 99%